Tight and early HbA1c control in patients with type 2 diabetes mellitus in Spain: quantifying the social value - María Merino; Paulina Maravilla-Herrera; Sara Artola; Sara Artola; Javier Escalada; Javier Escalada; Antonio Pérez; Antonio Pérez; Antonio Pérez; Juantxo Remón; José L. Trillo-Mata; Joan A. Vallès-Callol; et al. (Frontiers in Public Health)
IntroductionThe aim of this study was to estimate the social value of a tight and early control of patients with type 2 diabetes during the 5 years after diagnosis in Spain, compared to higher hemoglobin A1c (HbA1c) goals.MethodsAn economic model based on the scientific literature was used to estimate the 5-year social value of maintaining tight and early type 2 diabetes control, i.e., keeping HbA1c levels <6.5%, during the 5 years after diagnosis in Spain, compared to non-tight control. Areas of analysis included healthcare resource utilization, the presence of complications, quality of life, and mortality. The outcomes corresponding to these two types of control (tight vs. non-tight) were multiplied by their unit cost or financial proxy to obtain the economic impact associated with each type of control. Social value was estimated as the reduction in the economic impact of a non-tight control when tight control is implemented and maintained. The results are expressed in euros for the year 2021.ResultsThe economic impact of tight control during the first 5 years after type 2 diabetes diagnosis was estimated to be €1,010 million in Spain (€13,473 per patient), which is lower than the impact of non-tight control, which was estimated to be €1,127 million (€16,122 per patient) during the same period.ConclusionMaintaining tight and early control of type 2 diabetes during the first 5 years after diagnosis could generate a positive social value of €2,649 per patient over that period, in terms of better health outcomes, increased quality of life, and decreased premature deaths.